Plumbing Work in Green Market Based on Value Engineering - Indah Suci Rahayu (Jurnal KaLIBRASI - Karya Lintas Ilmu Bidang Rekayasa Arsitektur, Sipil, Industri, 2023)
The green traditional market concept begins with the structure of the market section. This concept consists of various ideas that make markets environmentally friendly, these ideas include composting buildings, open gardens, bathrooms/toilets, parking areas and planting in the market. Understanding Value Engineering in general is a management technique that uses a systematic approach, creative and organized effort that is directed to analyze the function of a system with the aim of achieving the required function at the lowest possible cost. However, this remains within the established technical functions and limits. The method used is value engineering with the aim of understanding and identifying obstacles in the application of value engineering and lean six sigma methods in dirty water installation work in market buildings with the concept of green building. The research instruments were arranged in the form of variables which were formulated in the form of questions (questionnaires). Cost efficiency was obtained in clean and dirty water installation work of a savings of 9.8%.